Occupational burn-out, fatigue and stress in professional rescuers: a cross-sectional study in Kazakhstan - Denis Vinnikov; Zhangir Tulekov; Gulnara Kapanova; Zhanna Romanova; Ilya Krugovykh; Sundetgali Kalmakhanov; Aliya Ualiyeva; Kaini Baigonova; Damet Ongarbaeva (BMJ Open)
Objectives To find predictors of burn-out in a cohort of rescuers.Design Cross-sectional study.Setting Republican Rescue Squad (N=105) and Republican Mudslide Rescue Service under the Ministry of Emergency Situations (N=480) in Almaty, Kazakhstan.Participants In total, we included 268 (80% men, median age 38 (IQR 22) years) rescuers from both organisations.Primary and secondary outcome measures We offered a questionnaire to rescuers, which included Maslach Burnout Inventory, quantifying emotional exhaustion (EX), cynicism (CY) and professional efficacy (PE) along with fatigue, stress and health-related quality of life (HRQL) tools.Results Lower scores of HRQL (Physical Component Score (PCS) beta −0.04 (95% CI −0.06 to −0.02); Mental Component Score beta −0.03 (95% CI −0.05 to −0.01)), higher fatigue (Fatigue Severity Scale (FSS) score beta 0.03 (95% CI 0.03 to 0.04)) and stress (Perceived Stress Score-10 beta 0.04 (95% CI 0.02 to 0.06)) independently predicted greater EX. Lower PCS (beta −0.03 (95% CI −0.06 to −0.01)) and FSS (beta 0.02 (95% CI 0.01 to 0.03)) could predict more CY burn-out. In addition to stress, higher education (beta 0.86 (95% CI 0.40 to 1.32)) was positively associated with lower burn-out severity in PE domain.Conclusions Fatigue, stress and HRQL were associated with burn-out in rescuers. Addressing these predictors may help guide further interventions to reduce occupational burn-out.